Maintaining Argument In Talk Show Interaction: A Pragma-Stylistic Inclination of Michelle Obama In Oprah Interview - Nurul Ulfa Nistiti; Slamet Setiawan; Ahmad Munir (Syntax Literate, 2022)
This research was taken from online media in the form of a Michelle Obama interview with Oprah Winfrey. First is Oprah's 2020 vision tour talk show. The talk show led by Oprah Winfrey tends to be more serious when discussing something that also affects the style of the conversations. Second, Oprah Winfrey Hold a Conversation on the United States of Women Summit by the white house. . The method used is descriptive qualitative by analyzing several utterances in Michelle utterances. This research accompaniment three research questions by analyzing the Pragmatic feature in Michelle Obama and the stylistic feature in Michelle Obama. Then the common patterns of Michelle Obama's arguments in her interviews. The results showed that Michelle maintains her argument through a pragmatic feature with adjacency pairs consisting of Q and A, Acceptance, Recognition, Agreement, and Approval. From a stylistic perspective, Oprah uses Hyperbole, Simile, Personification, Anaphora, and Parallelism. After the research compared both Michelle's interviews on Oprah's show, Michelle often uses the Agreement pattern and some of the figures of speech. During the research, researchers found the main idea of maintaining her argument. From maintaining that argument, the researcher also found three important points from Michelle's two interviews with her audience: Maintaining dignity, the importance of focusing on yourself, keep dreaming.